The Historian is a Creature of Civilizations that Disintegrate: a Diachronic Conversation Between Ernesto Volkening and Nicolás Gómez Dávil (2023)
This essay explores the fruitful dialogue on the nature of history recorded in Ernesto Volkening’s (1908-1983) Diario (1973) on the scholia of Nicolás Gómez Dávila (1913-1994). Despite the scholia and commentary being fragmentary, when read intertwined, an auspicious and coherent concept of history is manifested. In this dialogue, the historian, the historical fact, and the individual are central notions with respect to which historical thought is composed. As such, the scholia are illuminated by Voleking’s comments: who, against the ethereal solitude of the scholia, proposes concrete remarks on a historical event or a historian.